The Ecology of Health Service Utilization In Grenada, West Indies - Poland, Blake (My University, 1987)
It is widely accepted that the home environment may act as a socio-geographic focus of both disease transmission and of learned health behaviour. Households also appear to be units of convergence for factors identified in the literature as relating to the utilization of health services. This thesis is devoted to an examination of the role of the home environment, as well as of personal characteristics and accessibility, in the utilization of health services in Grenada, West Indies. The theoretical framework that informs this work is a holistic systems-orientated Socio-Ecological Model of Utilization. The empirical analysis draws upon the results of a detailed household survey conducted in five communities on the western portion of the island. Visits to homes containing children less than eight years of age isolated socio-demographic characteristics and information pertaining to residential mobility, household physical and behavioural environment, accessibility, self-reported morbidity and self-reported utilization. Records of patient visits over the previous two years for non-trauma events were abstracted from the medical records of area clinics, hospitals and physicians attending to the sample communities. Bivariate analyses between components of variables were conducted at both household and individual service use levels. These indicated that 1) service utilization was highly clustered around "high user" households and individuals; 2) considerable discrepancies emerged between self-reported and actual utilization; 3) the complexity of relationships between elements of the home environment was highlighted; and 4) there was a consistency with which certain elements of the home environment were statistically associated with health service use across a wide spectrum of illnesses. These observations were further confirmed in multivariate analyses, in which a small number of variables were able to retrospectively predict the presence or absence of service use by both adults and children with a high degree of model specificity and sensitivity. The implications of this work for development and health care planning in Grenada is discussed. The meaningful application of this work in Grenada is seen to hinge upon the extent to which relevant variables are amenable to change or act as proxy variables whose underlying nature of association with utilization remains to be adequately explored. A number of suggestions are advanced concerning the manner in which the study of health service utilization might be approached in the future.
Keywords: Grenada; Grenada, West Indies; West Indies; health service ultilization; ecology of health service utilization